1998
DOI: 10.1080/014186198254281
|View full text |Cite
|
Sign up to set email alerts
|

Estimating grain-size distributions in nanocrystalline materials from X-ray diffraction profile analysis

Abstract: It is well known that the Fourier analysis of X-ray di raction peak pro® les (as implemented by Warren and Averbach) can accurately determine the areaweighted average grain size of a ® ne-grained sample. Less well known is the fact that this method simultaneously yields a volume-weighted average grain size. Under certain circumstances, knowledge of these two weighted average grain sizes is su cient to permit reliable estimation of the grain-size distribution, even when the distribution cannot be calculated dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Nanocrystalline Pd pallets were prepared by inert-gas condensation and subsequent compaction (Krill and Birringer, 1998). Dark field TEM micrographs were evaluated quantitatively.…”
Section: The Correlation Between Crystallite Size or Size-distributiomentioning
confidence: 99%
See 1 more Smart Citation
“…Nanocrystalline Pd pallets were prepared by inert-gas condensation and subsequent compaction (Krill and Birringer, 1998). Dark field TEM micrographs were evaluated quantitatively.…”
Section: The Correlation Between Crystallite Size or Size-distributiomentioning
confidence: 99%
“…There is ample experimental evidence that the log-normal size distribution function, f ( x ), given by the median m and the variance σ , can describe crystallite size distribution in a wide range of bulk or loose powder materials (Valiev et al , 1994; Terwilliger and Chiang, 1995; Krill and Birringer, 1998; Ungár et al , 1999; Langford et al , 2000; Scardi and Leoni, 2002). Hinds (1982) has shown that with m and σ the arithmetic-, the area-, and the volume-weighted mean crystallite diameters are where k =0.5, 2.5, and 3.5 in the case of arithmetic-, area-, and volume-weighted mean and j stands for these different averages, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The size parameters and the effect of crystallite-size distributions on X-ray diffraction line profiles have recently been discussed in detail by Langford et al (2000). It has been shown by Krill and Birringer (1998) and Langford et al (2000) that by assuming lognormal size distribution functions f ( x ) for the case of spherical crystallites, the median and the variance of f ( x ), m , and σ 2 are directly related to the volume-weighted and the area-weighted column lengths, ✩ L vol ✪ and ✩ L area ✪, respectively:
Figure 3.Williamson-Hall plots obtained using the integral breaths of the diffraction profiles of MgO in five specimens after varied times at 700 °C.
✩ L area ✪=(2∕3) m ∙ exp ((5∕3) ln 2 ω ) and ✩ L vol ✪=(3∕4) m exp (7∕2 ln 2 ω ), where the normalized lognormal crystallite size distribution is given as: f ( x )=[√2 π ( ω ) x ] −1 exp {−[ ln ( x ∕ m )] 2 ∕2( ω ) 2 } and σ 2 = m 2 [ exp ( ω 2 ∕2)]∙[ exp ( ω 2 )−1].…”
Section: Resultsmentioning
confidence: 78%
“…The median and the variance of the crystallite-size distribution were obtained using the approach described in Krill and Birringer (1998). The results of the line profile analyses are listed in Table I.…”
Section: Resultsmentioning
confidence: 99%